Susceptibilidad a deslizamientos de la parroquia Chaquinal del cantón Pindal perteneciente a la provincia de Loja a escala 1:5000”. - Fernández Jiménez, Juan Carlos (2021)
The present investigation is research focuses on the use of the Saaty (1988) Hierarchical Multi-Criteria Analysis Process, which consists of a matrix analysis and involving value judgments through a matrix of the selected criteria, obtaining a weighting or consignment to the chosen variables. In addition to the application of Geographic Information Systems (GIS) to determine areas of susceptibility to landslides in the Chaquinal Parish, belonging to the Pindal canton of the Loja province. With this perspective, the susceptibility evaluation has been carried out based on a theoretical system, which consists of quantitatively evaluating the conditioning variables, which directly influence landslides to occur. As variables that constitute each of these thematic maps, geology is considered as a digital starting point of a DTM (Digital Terrain Model) for the topography and slope inclination map, considering the lithology present in the study area, the geomorphological units and the vegetation cover of the land. Where the landslide susceptibility zones have been correlated with a landslide inventory obtaining evidence that it is susceptible to landslides. In addition, an inventory of landslides was carried out to correlate these landslides found with the areas of susceptibility to landslides.